Utilization of Artificial Intelligence in CSR Programs for Supporting Regional Economic Development - Elizabeth Mutiara Putri Lubis; Gabyriella Uli T. Munthe; Hamonangan Siallagan (International Journal of Management and Business Economics, 2026)
Development digital technology has push change in various aspect activity companies, including implementation Corporate Social Responsibility (CSR). Utilization Artificial Intelligence (AI) in CSR programs is one of the potential innovation increase effectiveness, efficiency, and sustainability of social programs company in support development economy area. This article aim For analyze the role of AI in CSR program transformation, its contribution to empowerment economy society, as well as opportunities and challenges its implementation in support development economy area. The method used is study qualitative with approach studies literature ( library research), which was carried out through collection, study, and analysis various source scientific in the form of journal international and national, books academic, report institution international, as well as relevant publications with AI, CSR, and development economy area. Data analysis was carried out use technique analysis descriptive-qualitative For identify connection between AI utilization and effectiveness CSR implementation. Study results show that AI is capable transform implementation of CSR from a holistic approach administrative going to a more approach strategic and data -driven. The use of AI supports identification need public in a way more accurate, improve quality taking decision, strengthening implementation draft Creating Shared Value (CSV), as well as increase effectiveness of empowerment programs economy society, especially for MSMEs and development source Power humans. In addition, AI contributes in increase quality monitoring and evaluation of CSR programs so that can create impact more social and economic sustainable. The use of AI also has the potential speed up development economy area through strengthening innovation, improvement productivity and development economy based knowledge. However Thus, the implementation of AI is still face various challenges, including the digital divide, limitations literacy technology, high cost implementation, risk of algorithm bias, and issue ethics and data protection. This study conclude that AI has potential big For increase CSR contribution to development economy area if supported by good governance, collaboration multi-stakeholder, improvement capacity source Power humans, as well as implementation principle ethics in utilization technology. Therefore that, AI does not only functioning as tool technology, but also as instrument strategic that can strengthen effectiveness of CSR programs and encourage creation development better economy inclusive and sustainable